Designation and Multiobjective Optimization of a New Six-DOF Haptic Device Based on Genetic Algorithm - Shi, Baoyu; Wu, Hongtao (Wireless communications and mobile computing, 2021)
This paper focuses on designation and multiobjective optimization of a new haptic device. A new six-DOF hybrid haptic device has been designed combining series mechanism 3PRPaR and parallel mechanism ROBO_003.3PRPaR which is the positioning mechanism and ROBO_003 which is the directional mechanism. Screw theory was carried out to analyze the DOF of ROBO_003, aiming at the requirement performances of working space, stiffness, reverse drive, and output capacity of haptic device. Forward kinematics and inverse kinematics of the positioning mechanism were analyzed. To ensure the force transmission performance and compact structure, the evaluating indicator is dexterity and volume. Generalized coordinates as constraint condition, length of moving rod, and dexterity were chosen as the objective function. The parameters were optimized based on multiobjective optimization of the genetic algorithm. The paretooptimal solution set of the objective function was received. The results showed that the most suitable parameters are 0.502 rad. The optimized dexterity is 69% higher than the unoptimized, and the rod length is reduced by 6%.The research of this paper provides a theoretical basis for the designation of new haptic device.